Energy and Environmental Analysis of Solar Air Cooling with 2-Stages Adsorption Chiller in Jordan - Shahateet, Mohammed Issa; Albaali, Ghani; Saidi, Abdul Ghafoor (International Journal of Energy Economics and Policy, 2021)
The objectives of this study are to examine the use of the technology of Cooling Air by Solar Energy (CASE), which is used in air-conditioning applications to minimize the consumption of energy, as well as minimize CO2 emissions. The study also aims at providing an overview of different CASE technologies and analyzing the environmental feasibility of selected CASE technologies in Jordan. The methodology used involves a field study of one of the CASE technologies, which has been designed and developed in Jordan, to determine its technical feasibility. The environmental feasibility study has been done on the device used in this work in four scenarios. The results of the analysis of both energy and environmental feasibility have shown that the use of the CASE technology reduces greenhouse gases compared with Vapor Compression Chillers (VCC) that use electricity. Keywords: solar air-cooling; vapor compression chillers; greenhouse gases; energy analysis JEL Classifications: P18, Q40, Q43, Q51 DOI: https://doi.org/10.32479/ijeep.11701